Klippel Trenaunay Weber syndrome with unilateral polycystic kidney disease: a rare presentation - Charan, Shiv; Chander, Rakesh; Singh, Hasimran Jeet; Singh, Inderpal; Sehgal, Rishabh (International Journal of Research in Medical Sciences, 2016)
Klippel Trenaunay Weber syndrome (KTWS) is a rare disease characterized by hemihypertrophy, variceal enlargement of the veins, and arteriovenous (AV) malformations. Renal involvement in KTWS is not known except in rare case reports. Herein, we present a case of KTWS with unilateral polycystic kidney. A 52-year-old male was admitted due to pain left lumbar region for the last three months. The physical findings were increased diameter and increased length of the left leg compared with the right one, diffuse variceal enlargements on left leg, portwine stain on left side on neck, thorax, abdomen, left upper limb and left lower limb and a few hemangiomatous lesions on the left leg. Radiographic findings were cystic lesions in the left kidney, varicose veins in left leg, and hypertrophy of the soft tissues of the proximal left leg. Color Doppler of left lower limb showed incompetence of the saphenofemoral junction. He was diagnosed to have KTWS with these findings. Renal function tests of the patient were in the normal range. Patient’s only complain was left lumbar region pain, mild in intensity. Patient was managed symptomatically.